FRENCH SUBTITLING STRATEGIES AND TECHNIQUES USED IN INDONESIAN FILM MARLINA SI PEMBUNUH DALAM EMPAT BABAK - Aisyah, Tesyalia Zara; Budiman, Arif (UI Scholars Hub, 2023)
This qualitative research aims to describe the use of subtitling strategies and techniques in Indonesian film Marlina si Pembunuh dalam Empat Babak due to spatial constraints. The corpus consists of Indonesian audio script of the movie and its French subtitle. The theoretical framework is based on Gottlieb’s ten strategies of subtitling, and Carmitroglou’s, Carroll and Ivarsson’s codes of subtitling. The results indicate that out of ten strategies, one strategy, transcription, is not applicable to the corpus. The most common strategies are transfer, then condensation. Transfer is used to translate simple phrases, while condensation is used to translate dialogs with unimportant utterances. It is concluded that the genre of Marlina has a crucial role in the variation of used strategies. The dialogs in Marlina are short and fast tempo. Therefore, in order to create good subtitles, the use of those strategies become essentials for translators.